FIRST CLIACHITE AND FIND IN PACIFIC PELAGIC SEDIMENTS - Arkhipova L.D.; Galiy S.A.; Korsakov O.D.; Kruglyakov V.V.; Marushkin A.I. (My University, 1987)
Cliachite or alumogel (ALOOH + aq) is a gel-like, X-ray-amorphous aluminum hydroxide, and has so far been described only in bauxite and laterite, where it is mixed with boehmite, hydrargillite and diaspore and is primary relative to these minerals. It is assumed to form via coagulation of colloidal solutions of aluminum and by their conversion to a solid. The authors have discovered cliachite segregations in pelagic sediments of the Northeast Pacific Basin. They occur here very sporadically. Isolated cliachite grains were detected merely in 15 of the 600 sand-silt fractions examined, and only in one sample did cliachite account for as much as 38 percent of the silt fraction.